Immunohistochemical correlation of human adrenal nerve fibres and thoracic dorsal root neurons with special reference to substance P - Heym, Christine; Braun, Birgitta; Shuyi, Yin; Klimaschewski, Lars Peter; Colombo-Benkmann, Mario (Histochemistry and cell biology, 1995)
Applying a double-labelling immunofluorescence technique, six types of substance P-containing nerve fibres were distinguished in the human adrenal gland according to the immunohistochemical colocalization of (I) calcitonin gene-related peptide (CGRP), (II) cholecystokinin, (III) nitric oxide synthase, (IV) dynorphin, (V) somatostatin, and (VI) vasoactive intestinal polypeptide. Fibre populations I to IV in their mediator content resembled the respective subpopulations of primary sensory neurons in human thoracic dorsal root ganglia, while populations V and VI revealed no correspondence with dorsal root neurochemical coding. Nerve fibres with the combination substance P/nitric oxide synthase occurred only in the adrenal cortex, whereas all other fibre types were present in both cortex and medulla. As revealed by immuno-electron microscopy, substance P-immunolabelled axon varicosities (a) exhibited synaptic contacts with medullary chromaffin cells or with neuronal dendrites, (b) were directly apposed to cortical steroid cells and (c) were separated from fenestrated capillaries only by the interstitial space. These findings provide immunochemical support for an assumed sensory innervation of the human adrenal gland, and additionally suggest participation of substance P in efferent autonomic pathways. Furthermore, the results are indicative for a differentiated involvement of substance P in the direct and indirect regulation of neuroneuronal and neuroendocrine interactions.
Gesehen am 06.11.2025